A New Perspective Regard the Information System for Social Services (Global Journal of Human-Social Science, 2013)
The article aims at contributing to the debate about the introduction of ICT in social services with a reflection that, on the basis of the development of the ISSS of the Italian Autonomous Region of Friuli Venezia Giulia , shows that it is possible to set up an information system fill to the particular nature of social work and, in particular, to its methodology of work and to the complexity of social needs and of the relationship between social services' user and social worker. It points out that to get this result is important to give up the deterministic approach to technology as well as the centralized and top down approach to ISSS, and to adopt a relational approach to both these issues.
Keywords: information system; social work; new technology; community of practice; your keyword here